2017
DOI: 10.3847/1538-4357/836/2/203
|View full text |Cite
|
Sign up to set email alerts
|

Two-component Superfluid Hydrodynamics of Neutron Star Cores

Abstract: We consider the hydrodynamics of the outer core of a neutron star under conditions when both neutrons and protons are superfluid. Starting from the equation of motion for the phases of the wave functions of the condensates of neutron pairs and proton pairs we derive the generalization of the Euler equation for a onecomponent fluid. These equations are supplemented by the conditions for conservation of neutron number and proton number. Of particular interest is the effect of entrainment, the fact that the curre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 33 publications
0
48
0
Order By: Relevance
“…In this respect, the quantities we suggest to focus on to find experimental evidence of the presence of entrainment are much more suitable than trying to directly detect the current induced by one component on the other. It is worth mentioning that a recent experiment [52] was able to record the dynamics of both superfluid and normal fractions of a weakly interacting Bose-Bose mixture, as well as the finite temperature polarisabilities. We believe that experiments such as this one pave the way towards the detection of subtle superfluid effects such as the AB drag.…”
Section: Dynamic Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, the quantities we suggest to focus on to find experimental evidence of the presence of entrainment are much more suitable than trying to directly detect the current induced by one component on the other. It is worth mentioning that a recent experiment [52] was able to record the dynamics of both superfluid and normal fractions of a weakly interacting Bose-Bose mixture, as well as the finite temperature polarisabilities. We believe that experiments such as this one pave the way towards the detection of subtle superfluid effects such as the AB drag.…”
Section: Dynamic Stabilitymentioning
confidence: 99%
“…Despite its introduction was inspired by the problem of 3 He and 4 He superfluid mixtures, the low miscibility of these two fluids makes this system hardly achievable in experiments. The AB mechanism has instead recently found applications in the domains of astrophysics and of cold atom systems.…”
Section: Introductionmentioning
confidence: 99%
“…Chamel and Haensel showed that values of n np obtained from Skyrme interactions had a large spread [24], and in Ref. [14] the result for the SLy4 Skyrme interaction,…”
Section: Calculation Of Mode Frequenciesmentioning
confidence: 99%
“…For the nucleon contributions to the quantities E αβ we use the results of Hebeler et al [10], which were earlier employed in calculations of mode frequencies at long wavelengths [14]. In our numerical calculations we use values of E nuc αβ based on chiral effective field theory, because we regard these as the best available.…”
Section: Calculation Of Mode Frequenciesmentioning
confidence: 99%
See 1 more Smart Citation